Política fiscal e multiplicador fiscal no Brasil: teoria e evidência empírica (1997-2019) - Felipe Segateli Kohle Paulino (2021)
This dissertation estimates the fiscal multiplier in alternatives specifications of government spending and it aims to measure its impact and persistence on Brazilian economy. Given that the fiscal policy has played various roles in economic theory over the years in relation to economic growth theory, it is pertinent to understand its impact in economy. In its first section, this work dives into the history of the fiscal multiplier and its impact on economic growth theory in a capitalist system, emphasizing the development of fiscal policy theory. Subsequently, this dissertation presents an analysis of descriptive statistics of Brazil’s economy from 2003 to 2019, identifying the main features of fiscal policy. The last section of this dissertation works with the impulse response functions with time-varying coefficients (time-varying vector autoregression (tvVAR)) and with constant coefficients in a traditional Vector Autoregression (VAR). The fiscal multipliers were estimated in different specifications of federal government spending during the first quarter of 1997 until the fourth quarter of 2019. In both perspectives (tvVAR or VAR), the results suggest that the fiscal multipliers are more than one in the long run term for all specifications to government spending, supporting Keynesian findings on the economic literature about fiscal policy theory.